Postural balance impairment following arthroscopic rotator cuff repair in the early postoperative period: a prospective cohort study - İnci Hazal Ayas; Seyit Çıtaker; Ulunay Kanatlı (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background For patients undergoing arthroscopic rotator cuff repair surgery (RCR), it is crucial to prevent falls to minimize the risk of re-tearing the repaired muscles. Shoulder immobilization during the postoperative period may lead to a decline in postural balance. This prospective cohort study aimed to investigate the postural balance of patients in the early postoperative period following arthroscopic RCR. Methods Thirty-five patients (17 female/18 male, aged 49.56 ± 13.41 years) were assessed preoperatively, on the postoperative day 2, and at the postoperative week 6. Postural balance was evaluated using the Overall Stability Index (OSI), Antero-Posterior Stability Index (API), Medio-Lateral Stability Index (MLI), and Limits of Stability (LOS) tests conducted with the Biodex Balance System. Additionally, the Visual Analog Scale (VAS) pain score and Constant-Murley Score were recorded. Results The OSI and API values recorded on both postoperative day 2 and postoperative week 6 were statistically significantly worse than preoperative values. (p = 0.02, p = 0.03, respectively). Conversely, no statistically significant differences were observed across all three measurements for the MLI and LOS values (p > 0.05). The VAS score demonstrated a statistically significant decrease, while the Constant-Murley Score exhibited a statistically significant increase at the final measurement (both p < 0.001). Conclusion This study highlights that postural stability significantly declines during the early postoperative period following arthroscopic rotator cuff repair, with specific impairments in anterior-posterior stability, despite improvements in pain and shoulder function. These findings underscore the need for early, targeted rehabilitation interventions to address balance deficits and reduce the risk of falls, potentially improving overall recovery outcomes.